The Impact of the Extraction Method on Allanblackia floribunda Butter's Physicochemical Properties as a Possible Pharmaceutical Excipient. (10th April 2023) - Konadu, Mary; Johnson, Raphael; Osei, Yaa Asantewaa; Korang, James; Owusu, Frederick William Akuffo
Abstract : The extraction method of edible Allanblackia floribunda seed butter is crucial for preserving its constituents. The objective of the present study was to investigate the effects the extraction methods have on the physicochemical properties of A. floribunda butter regarding its potential use as a pharmaceutical excipient. Butter obtained from different extraction methods (including solvent/hexane, cold press, and traditional/hot water) was analyzed for its physicochemical properties such as yield, melting point, relative density, refractive index, moisture content, pH, acid value, saponification value, percentage of free fatty acids, and iodine value as well as beneficial elements and pathogenic microorganisms. All physicochemical parameters were within the standard limits for edible and industrial oils/butter (Codex Stan 210-1999) and were free from pathogenic microorganisms. However, the pH value of all extracts was higher than that of olive oil. The moisture content was higher in the water and hexane extracts compared to the cold-pressed ones. The hexane extract had higher mineral content (calcium, sodium, magnesium, potassium, and iron) than the cold press and hot water extracts. Extraction with hexane gave the highest yield. The identified fatty acids in all extracts are palmitic and stearic (saturated fatty acids), oleic, linoleic, and linolenic (polyunsaturated fatty acids) acids. Based on the physicochemical analysis, A. floribunda seed butter is edible and has the potential as a pharmaceutical excipient in drug delivery.